Investigating online football forums: a critical examination of participants' responses to football related racism and Islamophobia. (17th November 2022) - Kilvington, Daniel; Hylton, Kevin; Long, Jonathan; Bond, Alex
ABSTRACT: This article used a critical sampling approach to investigate a series of football forums which respond to and discuss racism and Islamophobia. A thematic analysis of 1, 064 forum posts identified 19 themes which led to the construction of five overarching themes which are: i) racism has decreased; ii) denying and downplaying racism and Islamophobia; iii) racism has increased; iv) victims and perpetrators; and, v) the action that should be taken. Our qualitative analysis illustrates that most of the football fans ascribe to a narrow understanding of racism in that it is perceived as overt. Very few forum participants offered a nuanced understanding of racism meaning that implicit racism, and how it can be challenged, was overlooked. While overt racism and Islamophobia was infrequently observed across the forums, fans' tendency to downplay racism, and distance themselves from it, was noteworthy as this acts as a barrier to the anti-racist action.